Spatially varying phytoplankton seasonality on the Northwest Atlantic Shelf: a model-based assessment of patterns, drivers, and implications. (3rd June 2021) - Zang, Zhengchen; Ji, Rubao; Feng, Zhixuan; Chen, Changsheng; Li, Siqi; Davis, Cabell S
Abstract: The signal of phytoplankton responses to climate-related forcing can be obscured by the heterogeneity of shelf seascapes, making them difficult to detect from fragmented observations. In this study, a physical–biological model was applied to the Northwest Atlantic Shelf to capture the seasonality of phytoplankton. The difference in phytoplankton seasonality between the Mid-Atlantic Bight (MAB) and the Gulf of Maine (GoM) is a result of the interplay between nutrients and temperature: In the MAB, relatively high temperature in the cold season and longer oligotrophic environment in the warm season contribute to an earlier winter bloom and a later fall bloom; in the GoM, low temperature and strong mixing limit phytoplankton growth from late fall to early spring, resulting in a later spring bloom and an earlier fall bloom. Although the temperature difference between the GoM and the MAB might decrease in the future, stratification and surface nutrient regimes in these two regions will remain different owing to distinct thermohaline structures and deep-water intrusion. The spatial heterogeneity of phytoplankton dynamics affects pelagic and benthic production through connections with zooplankton and benthic–pelagic coupling.